(untitled) (Revista de Psicología, 2017)
This descriptive-correlational research aims to evaluate working memory and long-term memory realted to written composition. Participants were 83 boys/girls aged between 9 to 11 of 4th and 5th grade from two public primary schools. Memory sistems were evaluated by Neuropsychological tests. Dimensions and structure of text guidelines were used to evaluate written composition. Results showed that working memory an long term memory performance were strongly related to children’s good quality compositions, specially when they are coherent and cohesive. The study provide findings that may contibute to show the predictive value of neurpsychological processes in writing skills acquisition.